Utilization of NYPA (NYPA furticans) palm frond as a potential for bio-ethanol - Abdullah, Arman; Abdullah, Syamsul B.; Samah, Rozaimi Abu; Mohd Zahari, Mior Ahmad Khushairi; Md Zain, Wan Salwanis (2017)
Bioethanol has been gaining much interest recently in terms of research and development. Since there are various factors such as rising oil price, environmental issues and high rate consumption of fossil fuel, the global demand for bioethanol has shown a remarkable increase. This aim of this study was to discover the potential of Nipa palm frond juice as a sustainable potential feedstock for production of bioethanol. Nipa palm frond is known to contain high sugar for production of bioethanol. NPF was obtained from Kg Miang, Pekan and the juices were extracted by pressing the fresh NPF using the conventional sugarcane pressing machine. The NPF juice contains higher glucose content, which is about 70% of the total free sugar. Hence, it has a high potential to be the carbon source for producing bioethanol. In this study, bioethanol was produced by fermentation using Sacchromyces cerevisae. The parameters investigated in this research work are incubation temperature, pH of NPF juice, concentration of NPF juice, incubation time and agitation speed. The experimental design was planned using 2-level factorial with the aid of Design Expert Software 7.1.6. The sugar concentration was analysed by HPLC while ethanol concentration from the fermentation sample was analysed using GC-FID. Using the ethanol concentration obtained from GC-FID analysis, the main factors affecting ethanol fermentation were screened using factorial analysis and best condition for the production of bioethanol was suggested. The validation experiments were conducted based on one suggested best condition from Design Expert 7.1.6 in triplicate. Based on the Pareto chart, the best main parameters influencing ethanol yield were incubation temperature, concentration of NPF juice and incubation time. Highest ethanol yield produced was found to be 1.541 g/L with the condition of 12 hours fermentation, 32 °C, pH 4, and 160 rpm with 100 % juice concentration. The lowest ethanol yield was 0.562 g/L with the condition of 24 hours incubation time, 25 °C, pH 7, and 80 rpm with 50 % juice concentration. The models with the selected effects were analyzed using analysis of variance (ANOVA) and found significant with high correlation (R2 = 0.9944) between the experimental data and model data was obtained. The best condition for ethanol production suggested at 12 hours, 32 °C with pH 4, 160 rpm and 100 % juice concentration. The validation experiments were conducted at the suggested best conditions and the error from these runs were 3.2 %, 1.7 %, and 3.7 %. Based on the predicted and experimental results presented, the experimental values were in good agreement with the predicted values proposed by the model with an error less than 10 % and proved to be an adequate model.